MODIFICATION OF TRIGGER SYSTEMS ON THIRD POWER ELECTRICAL CONTROL OF MEDANG VEDC PHASE - Haryanto Haryanto; Sunomo Sunomo (Jurnal Penelitian Saintek, 2006)
AbstractThe fault   of the pulse  transformer   and  the  TCA  785  triggering   systems  in themodule   of  Power   Electronics    made   by   VEDC   Malang   make   it  difficult   tosubstitute  due to the high prices  and unavailability   in Yogyakarta  market.The purpose   qf this  application   research   is to substitute   of  TCA  785 with  twooutputs   by  two  pieces   of  NE  555  which   work   in  the  same   manner,   and  tosubstitute   ofpulse    transformer  for  SCR  and  TRIAC  phase  control  (firing)  withoptocoupler    MDC   302/    in   module    501  for    laboratorium    practicum:    Themodification   is needed  because  of unavailability   of the  two components   and theprice.  For  three phase  control,  the system  need  three pieces  of both  TCA  785 '.I'and pulse  transformers.   So,  the substitution   needs  six pieces   of both  NE  555 '.I'and MOC302I   '.1'.   Using of optocouplerfor    coupling  offiring   the SCR '/TRlAC '.I'is to avoid  induction  voltage from   the main  to the  controlling  part  system  whenthere is afault   or short circuit  in the main system.This experiment   applied  to the SCR firing   of  0"-180" phase  control  and  to theTRIAC  of U' -180" and  180" -360" phase  control.  in this action.  the performanceofthe   NE555's   and the MDC  3021 '.I'   must  be the same  of the  TCA  785 and thepulse  transformer.The  result   shows   that   without   the   compensation    circuit   of  main   networksynchronization,    NE  555 's have  good  performance   for   SCR  half  wave  phasecontrol.   For  TRIAC  phase  control,  the  control  of positive   and  negative  cycledone in serial  manner,  not in the same period,  the first  action  is/rom   (/' to 180",and  then followed  from   180" to  360".  With  the  compensation    circuit  of  mainnetwork  synchronization,   the  behavior  offiring    111 phase  control  has  the same manner  with  TCA 785 but notforfiring     of 0"-45"  The cause  is comingfrom    the fact  that  the firing  signalfrom    the of NE 555  is done  by the rear  of the  output pulses.    and   the   histeresis    of   serial   synchronization     system   for    NE   555 triggering      To   improve    the   performance,      new   design    of   main   network synchronization   is needed,  that work in the leading  scheme  of zero crossing.